Wild pig (Sus scrofa) as prey of the Common Vampire Bat (Desmodus rotundus) - Hernández-Pérez, Edwin L.; Castillo-Vela, Guillermo; García-Marmolejo, Gabriela; Sanvicente López, Mauro; Reyna-Hurtado, Rafael (THERYA, 2019)
The common vampire bat (Desmodus rotundus), is the hematophagous bat with the broadest distribution and the only one that preys on wild mammals. However, when the abundance of domestic species increases, D. rotundus tends to feed on horses, domestic pigs, and poultry. The presence of Wild pigs in Laguna de Términos, Campeche, represents an increase in prey availability, a factor that fosters the growth of bat populations in the region. Records were obtained with camera traps in the area of influence of the Laguna de Términos Flora and Fauna Protection Area, Campeche. Camera traps were placed on trees at the edge of trails for the recording of Wild pigs (Sus scrofa) and collared peccaries (Pecari tajacu). The photo trapping period ranged from January 25 to August 16, 2018 with a sampling effort of 1,428 trap days. We recorded 18 species of mammals in the five locations studied. Predation of the common vampire bat on Wild pigs was recorded in a single camera trap located in an oil palm plantation (Elaeis guineensis) surrounded by livestock areas and secondary forest fragments. Wild pigs were the only species recorded as being attacked by the common vampire bat. Of all separate records of Wild pigs, 11.7 % (n = 22) corresponded to photographs and videos of interactions between Wild pigs and bats. Vampire bat attacks were recorded between 20:00 and 5:00 h, with a peak of activity around 23:21 h. The increased availability of Wild pigs, together with changes in land use, seemingly foster the growth and expansion of vampire bat populations and, therefore, contribute to a higher incidence of attacks on domestic species. In addition to the negative ecological effects, the presence of Wild pigs involves increasingly important epidemiological implications. Studies on the interaction between common vampire bats and Wild pigs are necessary to assess the risk of disease transmission in the region.